2023
DOI: 10.1007/s00216-023-04921-2
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Hydrophobicity of Paper Substrates for Effective Colorimetric detection of Glucose and Nucleic acids

Sujesh Sudarsan,
Prashil Shetty,
Raja Chinnappan
et al.

Abstract: This study investigated the colorimetric response of standard glucose, serum glucose, and nucleic acid assays on various paper surfaces with different wettability, including hydrophilic, hydrophobic, and nearly superhydrophobic surfaces. Water contact angles (WCA) formed by water droplets on each surface were measured using ImageJ software. The hydrophilic surface showed no contact angle, while the hydrophobic and nearly superhydrophobic surfaces exhibited contact angles of 115.667° and 133.933°, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The interaction between the hydrophobic surfaces and the microbes in the urine sample can be utilized for concentrating the microorganisms. Tuning the hydrophobicity surfaces was acting as a sensing platform for the detection of nucleic acid and other metabolites ( Sudarsan et al, 2023 ; Uttam et al, 2024 ). A similar methodology was used for the isolation of exosomes.…”
Section: Exosomal Rna Biomarker Isolation Strategiesmentioning
confidence: 99%
“…The interaction between the hydrophobic surfaces and the microbes in the urine sample can be utilized for concentrating the microorganisms. Tuning the hydrophobicity surfaces was acting as a sensing platform for the detection of nucleic acid and other metabolites ( Sudarsan et al, 2023 ; Uttam et al, 2024 ). A similar methodology was used for the isolation of exosomes.…”
Section: Exosomal Rna Biomarker Isolation Strategiesmentioning
confidence: 99%
“…24,25 Numerous studies have exploited PADs to develop point-of-care and POU testing platforms. 26 Such testing systems have been performed using immunosorbents, 27 molecularly imprinted sorbents, 28 or hydrophobic paper 29 coupled with colorimetric or spectrofluorimetric detection. Nevertheless, we performed a literature survey that revealed that no PAD is available for the POU determination of the water content in ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…To address the above issues, cellulose-based devices have garnered a significant amount of attention over the past few decades (Mani et al 2019;Prabhu et al 2020b;Hasandka et al 2021;Prabhu et al 2021;Kelkar et al 2022). Recent developments in cellulose-based microfluidics have significantly helped to identify adulterants, pathogens, and other analytes in a cost-effective way (Prabhu et al 2020a;Mani et al 2020;Hasandka et al 2022;Ray et al 2022a;Selvam et al 2022), without the need for sophisticated techniques and with exploration of different methods for sensitivity enhancement (Mani et al 2013;Sudarsan et al 2023aSudarsan et al , 2023b. Herein, frugal devices are made from paper or other porous materials (such as threads), that manipulate small (10 −6 to 10 −9 L) volumes of fluids by capillary action (Nishat et al 2021;Ray et al 2022b).…”
Section: Introductionmentioning
confidence: 99%